Prospect of clean coal for sustainable energy mix in Malaysia - Salleh S.F.; Al-Amin A.Q.; Abdullah T.A.R.T. (Inderscience Publishers, 2023)
Coal; Emission control; Energy policy; Environmental impact; Fossil fuels; Greenhouse gases; Sustainable development; Clean coal; Economic sustainability; Effective energy; Energy; Environmental issues; Fuel diversification; Malaysia; Sustainable energy; Coal industry